Implementasi Handover Sbar Pada Perawat di Ruang Rawat Inap Sebagai Upaya Peningkatan Kualitas Pelayanan - Rezkiki, Fitrianola; Kartika, Imelda R; Nadia, Sri; Susanti, Nadia (FKM UIN Sumatera Utara Medan, 2023)
SBAR handover for nurses is an indicator of the quality of hospital services. SBAR handover quality in nurses affects patient satisfaction, patient safety, and length of patient stay. In its implementation in the field, this method has not been widely used or has been used but has not been maximized, there needs to be focused training so that it can provide good quality SBAR handovers.This PKM aims to increase the knowledge and skills of nurses about SBAR Handover in the inpatient room one of the government hospitals in Bukittinggi city. The method used in this PKM includes dissemination of knowledge related to SBAR Communication during nurse handovers, socialization of SBAR Handover SOPs and Roleplay. The results of this PKM obtained an increase in the knowledge and skills of nurses in carrying out SBAR Handovers, as well as the creation of SOPs for implementing Nurse Handovers with SBAR Communication. From the results of monitoring and evaluating PKM activities, it is known that nurses understand and are able to practice independently implementing the SBAR Handover in each shift. It is hoped that this activity can continue to be improved by inaugurating the SOP and supervision of the head of the room so that nurses are competent in SBAR Handover as an effort to improve the quality of health services in hospitals.